Optimization of protein extraction from Aspergillus nidulans for gel electrophoresis - N Osherov; G S MAY (Fungal Genetics Reports, 1998)
Efficient extraction of proteins from filamentous fungi is difficult both as a result of high endogenous protease activity, the existence of a hard cell wall, and the tendency of hyphae to clump. We have had difficulty using published protocols in extracting high molecular weight proteins (>150 kDa), and in extraction from germlings grown on minimal media with a poor carbon source such as glycerol. In order to address these problems, we have compared several different extraction protocols and found the protocol utilizing 9M Urea-sample buffer to be the fastest and most efficient with sample variation being kept to a minimum.